1230 PALLIATIVE CARE MOVEMENT DISORDERS MULTIDISCIPLINARY MEETING. (16th January 2023) - Davies, R; Wilson, E; Richfield, E; Mundy, C; Wright, B; Stratton, E
Abstract: Introduction: It is well recognised that patients with Parkinson's disease (PD) have significant symptom burden in advanced stages of their disease. Integration of movement disorder and palliative care services has been limited by concerns about resource and sustainability. We present our experience of establishing a movement disorders palliative care multidisciplinary meeting. Method: In 2019 we established a multidisciplinary virtual bimonthly meeting between movement disorders and palliative care specialists. Referrals were accepted from movement disorder specialists, community Parkinson's practitioners and palliative care specialists. Referring clinicians all actively applied primary palliative care approaches within their existing services. Aims of the meeting were to facilitate holistic management of complex needs, support advance care planning (ACP) and consider referral to specialist palliative care services. Result: 37 patients in total were discussed over a 2-year period (although the service was limited for a time due to COVID pressures). On average 3 new patients were discussed per meeting. Reasons for referral included motor and non-motor symptoms, support with ACP, medication advice, caregiver concerns and emotional distress. Meeting outcomes included medication adjustments, expediting reviews, hospice support, carer support, and referral to other services. Since the meetings started 23 (62%) patients have died. Of these, 30% died in hospital compared with the national average of 43.4%. The average between discussion at the meeting and death was 139 days. The meeting has generated education opportunities, triggered joint assessments and a professionals' framework for the palliative management of patients with a movement disorder. Conclusions: We present the experience of an MDT embedded within an early integrated palliative care service for movement disorders. The MDT has strengthened partnership working and findings suggest that alongside active primary palliative care, specialist palliative care for PD can be sustainable and resource efficient in a UK setting.